FINANCIAL CONTROL KEY ELEMENT TO PROVIDE ECONOMIC SECURITY OF THE ENTERPRISE - Demchuk, N. I.; Tkachenko, H. A. (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2019)
The article considers the essence of financial control and its importance in ensuring the economic security of the enterprise. It has been established that financial control is an effective coordinating system for ensuring the interconnection between the formation of an information base, financial analysis, financial planning and internal financial control, which ensures concentration of control activities. In the most priority areas of financial activity of the enterprise, timely detection of deviations of its actual results from the foreseen and the adoption of operational management decisions that ensure its normalization. The views of leading scientists concerning the definition of the concept of financial controlling and its key elements are researched. Also, the key financial control functions are analyzed and analyzed in the article. Six main concepts of financial controlling used for realization of functions of financial control in crisis conditions of management. The concept of generation of integrated planning and control tools; concept of production, sale or service; the concept of taking into account the specifics of the enterprise; the concept of the orientation of the movement of funds; use of the tools of the concept of financial control as the basis for making managerial decisions; management concept and management decision making. The effectiveness of the company in difficult conditions, and especially in the long run, means not just survival in the market, but also ensuring high rates of development and competitiveness, is determined by the level of financial potential and quality of financial management in the enterprise. Which is provided by a certain extent with the effective organization and implementation of the financial system controlling. The application of the financial controlling system at the enterprise will enable to prevent emergence of crises, to identify the causes of financial problems and to effectively search for solutions to them. the primary task of financial control is the maintenance of liquidity and solvency of an enterprise, which can be achieved under the condition of financial planning with the current analysis of financial sustainability.